2022
DOI: 10.1038/s41467-022-32764-5
|View full text |Cite
|
Sign up to set email alerts
|

Adipocytes control food intake and weight regain via Vacuolar-type H+ ATPase

Abstract: Energy metabolism becomes dysregulated in individuals with obesity and many of these changes persist after weight loss and likely play a role in weight regain. In these studies, we use a mouse model of diet-induced obesity and weight loss to study the transcriptional memory of obesity. We found that the ‘metabolic memory’ of obesity is predominantly localized in adipocytes. Utilizing a C. elegans-based food intake assay, we identify ‘metabolic memory’ genes that play a role in food intake regulation. We show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 77 publications
1
9
0
Order By: Relevance
“…Thus, neonatal AgRP ablation might have reduced survival in OFR mice by reducing food intake, at least in part. The observed trend for OFR ablated mice to eat less during restriction is consistent with our previous work showing that obese WAT transplants contain specific factors that can encourage feeding (34).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Thus, neonatal AgRP ablation might have reduced survival in OFR mice by reducing food intake, at least in part. The observed trend for OFR ablated mice to eat less during restriction is consistent with our previous work showing that obese WAT transplants contain specific factors that can encourage feeding (34).…”
Section: Discussionsupporting
confidence: 92%
“…Weight loss through dieting is frequently followed by weight regain due to compensatory changes that encourage a higher body weight (30)(31)(32)(33). Body weight recidivism following dieting was recently suggested to be driven by a "metabolic memory" of obesity, which predominantly resides in WAT (28,34). Specifically, gene expression and metabolites within metabolic tissues were compared between lean, obese, or previously obese mice; obesity induced widespread transcriptional and metabolomic changes that were reversible by weight loss across most metabolic tissues, except for WAT (34).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, obesity is intricately intertwined with glycemic and metabolic homeostasis, as evident in previous studies (El-Mesallamy et al 2013 ; Aboouf et al 2015 ; Khella et al 2017 ). However, Zapata et al ( 2022 ) also observed that obesity elicits a persistent metabolic imprint that persists despite weight loss, phenotypically resembling metabolic memory. Despite this, the existing literature consistently associates metabolic memory with glycemic fluctuations.…”
Section: Overview Of Metabolic Memorymentioning
confidence: 99%
“…Adipogenesis plays a central role in determining AT mass and functions. Recent studies revealed vacuolar H + -ATPase (V-ATPase) subunits ATP6AP2 and ATP6V0A1 regulates adipogenesis and adipose functions 11 , 12 . V-ATPase is highly conserved and expressed in virtually all eukaryotes as a multi-subunit complex, composed of a transmembrane V o domain (subunits a, c, c', c'', d, e) that transports H + across membrane, and a cytosolic V 1 domain (subunits A-H) responsible for ATP hydrolysis.…”
Section: Introductionmentioning
confidence: 99%